Design and Characterization of Sustained Release Mucoadhesive Microspheres of Tolterodine Tartrate - Swain, Suryakanta; Meher, Dusmant; Niranjan Patra, Chinam; Sruti, Jammula; Chandra Dinda, Subas; Bhanoji Rao, Muddana Eswara (Current Drug Delivery, 2013)
The work was aim to design and characterize the sustained release mucoadhesive microspheres of Tolterodine tartrate prepared by non-aqueous solvent evaporation technique using ethyl cellulose based selected mucoadhesive polymers. Selected microspheres formulations of were found to be discrete, spherical and free flowing from the preliminary formulations. The microspheres exhibit good mucoadhesive property in in-vitro wash off test and showed high drug entrapment efficiency. Tolterodine tartrate release from these microspheres was slowed, extended and depended on the concentration of ethyl cellulose and type of mucoadhesive polymer used. In vitro drug release studies suggested that formulation F6c showed consistent drug release for up to 24 h time period. Among all the formulations, F6c containing ethyl cellulose with chitosan showed the reproducible results with best mucoadhesive profile and good surface morphology. The correlation value (r2) indicated that the drug release followed Higuchi model. Analysis of variance (ANOVA) showed significant difference in the release of drug from all formulations at P < 0.05 level. Accelerated stability study of optimized formulation (F6c) up to 3 month showed there was no change in drug content and release characteristics during storage.
Keywords: swelling index